Evaluasi Penerapan Pengendalian Internal atas Proses Bisnis Pendapatan Jasa: (Studi Kasus pada Perusahaan Depo Peti Kemas) - Desi Ikaputri; Eliza Fatima (Owner : Riset dan Jurnal Akuntansi, 2023)
Revenue business processes are the primary key for a company to generate profits as a financial performance target. In its implementation, it must be supported by a clear internal audit function and accounting information system with an effective level of control in all business processes to produce accurate and quality data or information, as well as increase the effectiveness of the company's operational activities. However, if these factors do not support it, all personnel will work by habit factor, and management will face the risk of loss. This study aims to analyze the condition of PT X’s internal control and aspect that can be improved in optimizing internal control over the performance and reporting of the company's revenue business processes. The research method used is descriptive qualitative with a case study approach at PT X, a container management company, that previous research on this field of business is still limited. The data sources were derived from observation, a series of interviews with the management, and an analysis of internal documents. The results show that there were weaknesses in the procedures for implementing revenue business processes caused by the absence of adjustments to clear and documented recording procedures, unstructured implementation of control activities, and not being supported by an adequate information system. Therefore, this study provides recommendations for corrective actions to optimize the performance and reporting of the company's revenue business processes.